PENGARUH STRUKTUR MODAL, KEBIJAKAN DEVIDEN, DAN INFLASI TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Otomotif Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2015-2017) - Danang Laksono; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe purpose of this study was to determine the effect of Capital Structure, Dividend Policy, and Inflation on Company Values (Study on Automotive Companies Listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 Period). The population of this study uses 13 automotive companies listed on the Indonesia Stock Exchange for the period 2015-2017. Determination of the sample is based on the purposive sampling method, using the sampling criteria as follows, the automotive companies listed on the Indonesia Stock Exchange for the period 2015-2017, companies that publish annual reports and financial statements for the period 2015-2017. Based on those sample’s criteria the entire populations is used in this study sample. The data analysis technique in this study uses multiple linear regression methods and classical assumption tests by testing hypotheses using the t test. Analysis tool using SPSS 21. The results of this study indicate that the Capital Structure has a positive and significant influence on Company Value. Dividend Policy has a positive and significant influence on Company Value. While inflation does not have a significant effect on the value of the company.Keywords: Capital Structure, Dividend Policy, Inflation and Corporate Value